Reviewing Colchicaceae alkaloids - perspectives of evolution on medicinal chemistry - Larsson, Sonny; Rønsted, Nina (Current topics in medicinal chemistry, 2014)
The subject of chemosystematics has provided insight to both botanical classification and drug development. However, degrees of subjectivity in botanical classifications and limited understanding of the evolution of chemical characters and their biosynthetic pathways has often hampered such studies. In this review an approach of taking phylogenetic classification into account in evaluating colchicine and related phenethylisoquinoline alkaloids from the family Colchicaceae will be applied. Following on the trends of utilizing evolutionary reasoning in inferring mechanisms in eg. drug resistance in cancer and infections, this will exemplify how thinking about evolution can influence selection of plant material in drug lead discovery, and how knowledge about phylogenetic relationships may be used to evaluate predicted biosynthetic pathways.